Student engagement techniques : a handbook for college faculty - Barkley, Elizabeth F (Jossey-Bass, 2015)
From the Publisher: Keeping students involved, motivated, and actively learning is challenging educators across the country, yet good advice on how to accomplish this has not been readily available. Student Engagement Techniques is a comprehensive resource that offers college teachers a dynamic model for engaging students and includes over one hundred tips, strategies, and techniques that have been proven to help teachers from a wide variety of disciplines and institutions motivate and connect with their students. The ready-to-use format shows how to apply each of the book's techniques in the classroom and includes purpose, preparation, procedures, examples, online implementation, variations and extensions, observations and advice, and key resources.